PERANAN GENERASI Z DALAM PENERAPAN RESPONSIBLE TRAVELING UNTUK PARIWISATA BERKELANJUTAN - Bayu Yudistia; Endang Sri Wahyuni; Muh. Ilham H (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to find out the role of Generation Z in implementing responsible traveling for sustainable tourism. Generation Z is defined as individuals born between 1995 and 2012. This generation is environmentally conscious and has a high concern for social issues. This research uses a qualitative approach. Data collection was done by observation, interview, and documentation. Secondary data was obtained from various sources such as digital literacy and research journal reference sources. Primary data was obtained by semi-structured interviews with generation Z tourists and local communities who often conduct travel activities to explore the opinions and knowledge of informants about how generation Z's role in the application of responsible traveling for sustainable tourism. The result of the research is that generation Z have an important role in the application of responsible traveling for sustainable tourism. Generation Z has high knowledge and awareness of the importance of sustainable tourism. Generation Z is also active in various sustainable tourism activities, such as nature tourism, educational tourism, and cultural tourism. This research shows that Generation Z has an important influence on others in terms of the implementation of responsible traveling. Generation Z often promotes sustainable tourism to their friends, family and followers on social media. The results concluded that generation Z has an important role in the application of responsible traveling for sustainable tourism. Generation Z have important knowledge, awareness and influence to encourage more environmentally friendly and sustainable tourism